Design of Ergonomic Work Facilities to Reduce Skuble Muscle Disorders with Quick Exposure Check (QEC) Method in CV. XYZ - Endang Pudji Widjajati; Mega Cattleya Prameswari Annissaa Islami; Eko Wahyudi (Future Science)
Work facilities can affect an operator. Unsafe and comfortable work facilities can reduce operator performance and pose a risk of work accidents. CV. XYZ is a business entity engaged in contracting and advertising services. Every day, operators work with non-ideal body positions (bent, sit down) which affects their performance in fulfilling work and causes disturbances in the skeletal muscles of work-related musculoskeletal disorders (WMSDs). It is necessary to review the work facilities for operators. This study aims to design an ergonomic work facility to reduce skeletal muscle disorders at certain work stations based on an evaluation using the Quick Exposure Check (QEC) method. The results showed that the highest average exposure level value was found in the workstation on the raised letter work, which was 71.60%, so it was necessary to make changes to the workstation. The proposal given is in the form of a chair and table design for operators using anthropometric data. The new design is expected to reduce the risk of injury to the operator's work, especially injuries to the skeletal muscles, and improve the performance of the workers themselves.